Age distribution of patients with multiple High-Risk Human Papilloma Virus (HR-HPV) genotypes and HPV vaccine recommendations by age - Nil Tekin; Gülçin Çetin Uysal (SERNEV, 2024)
Introduction: The aim of this study to identify the age distribution of patients with multiple high risk Human Papilloma Virus (HR-HPV) genotypes and to evaluate HPV vaccination programs through age distribution. Methods: Patients between the ages of 20-70, who had cervical screening (cervical smear) and HPV genotype tests between January 2017 and December 2021 in Gynecology and Obstetrics Department in Tınaztepe University Hospital, were included in this study. HR-HPV genotype tests and age information which were performed evaluated retrospectively. Results: The study consisted of 66 patients analysis with multiple HR-HPV genotypes. The median age of the patients with multiple HR- HPV was found to be 32.6 years old. The most frequent combination of multiple HR-HPV was found two sub-types of HR-HPV (66.7%), median age was found as 36.6 years old. In this study the frequency for three sub-types of HR-HPV was found 24.2% and median age for this group was found to be 34.7years old. We found frequency in patients with four or more sub-types of HR-HPV as 9.1%, and the median age for this group as 33.1 years old was found. Conclusion: The most common cause of cervical cancer is HPV infection. Multiple HR-HPV infection progression may promote high risk cervical lesions and neoplasia. HPV genotype testing results considering combination of subtypes may direct individual treatment, follow-up protocols for patients. HPV vaccination research may comprise multiple HR-HPV subtypes relations and age distribution for optimal immunization.